OPPORTUNITIES FOR ORGANIZING CHORAL PERFORMANCE IN MUSIC LESSONS OF GENERAL SECONDARY SCHOOLS - Rakhimov Ravshan Naimovich; Rahmatullayeva Feruzabonu Zarifovna (Ecominds Press, 2026)
The article examines the ways of organizing choral performance in music lessons of general secondary schools, vocal voice development, singing culture, the formation of students’ musical emotions, spiritual world, deep philosophical and social thinking. It also analyzes the valuable ideas of Eastern thinkers Al-Farabi and Ibn Sina, as well as the Greek philosopher Plato, concerning the interrelation between musical education and moral upbringing, and the spiritual maturity of an individual. In addition, the decrees of the President of the Republic of Uzbekistan on the development of national music are reviewed.
Keywords: Vocal-choral, music, aesthetics, musical sound, morality, thinker, vocal voice, beauty, live performance.